Tazkirah ramadhan series - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
To enlighten the spirit of Ramadhan, CMLHS organised Tazkirah Ramadhan Series every Friday morning. Three speakers were invited to deliver a talk on various topics.